Automobile parts modification systems(ModifiCARtor) / Ahmad Riyadh Abu Bakar - Ahmad Riyadh, Abu Bakar (2003)
This project document been written for Latihan Ilmiah 2 (WXES3182) in order to accomplish the need of graduation structure of Bachelor of Computer Science (Software Engineering) of University of Malaya. This document been written with the practice of knowledge learned from the Faculty of Computer Science and Information Technology, University of Malaya. The difficulty and challenge that have been faced through out the project is all about to give the student experience how the real software development world works. lts also give a chance for student to practice what they have learned before entering working environment.